The Panama Railroad - Pyne, Peter (Book collections on Project MUSE., 2021)
"In 1848, a group of ambitious American entrepreneurs decided to embark upon a remarkable engineering feat-they would build a railroad across the Isthmus of Panama to connect the Atlantic and Pacific Oceans. The creation of the Panama Railroad ranks as one the boldest capitalist ventures in the nineteenth century, and would require battling climate, disease, and geography before it was completed. On a human level it would transform the destiny of thousands of lives in America and Panama as well as in Ireland. The Panama Railroad provides the first comprehensive account of the railroad's construction, going well beyond the known stories of the titans of industry involved with its construction, such as William Aspinwall, George Law, and Cornelius Vanderbilt. It seeks to correct false claims and address numerous gaps in past histories, and in particular showcases the stories of the ordinary Irish workers willing to travel halfway around the globe to pursue an uncertain future and a perilous undertaking in the hopes of escaping the devastating Great Famine of 1845-49"--